Predicting methane emission of dairy cows using milk composition - Gastelen, Sanne van (Wageningen University, 2017)
Enteric methane (CH4) is produced as a result of microbial fermentation of feed components in the gastrointestinal tract of ruminant livestock. Methane has no nutritional value for the animal and is predominately released into the environment through eructation and breath. Therefore, CH4 not only represents a greenhouse gas contributing to global warming, but also an energy loss, making enteric CH4 production one of the main targets of greenhouse gas mitigation practices for the dairy industry. Obviously, reduction of CH4 emission could be achieved by simply reducing livestock numbers. However, the global demand for dairy products has been growing rapidly and is expected to further grow in the future. Therefore, it is critical to minimize environmental impact to produce high-quality dairy products. The overall aim of this PhD research was, therefore, to develop a proxy for CH4 emission that can be measured in milk of dairy cows.